MEASURES OF FINANCIAL REGULATORS IN THE FIELD OF INTERNATIONAL CAPITAL FLOWS CONTROL - Yevhen Bublyk (Izdevnieciba "Baltija Publishing", 2021)
The article attempts to identify new trends in approaches to assessing the impact of uncontrolled international capital flows on the development of the national economy and the corresponding changes in regulatory policies. It is pointed out that uncontrolled capital flows pose a special threat to small open economies due to insufficient development of the institutional environment and low depth of financial markets. There has been constructed circle of typical for small open economies risks, conducted with uncontrolled capital flows movement, such as deepening structural imbalances in financial asset markets, undesirable excessive fluctuations in the national currency rate, the flight of national capital and the erosion of the tax base. Based on the analysis of recent research, international regulatory initiatives of EU countries, recommendations of international development institutions and IMF's Integrated Policy Framework, have been identified such trends as strengthening control over illegal capital flows, limiting of the negative speculative influence, panic and herd behaviour on exchange rate stability. Argued for a very important role which plays an uncontrolled dynamics of national currency rate on the transmission of global shocks to national economies. This necessitates a serious overhaul of exchange rate policy approaches. Central banks of small open economies should consider exchange rate stability as one of their goals. This does not mean inflation targeting abandon. The use of the instrument of currency interventions helps to influence the achievement of external targets, increasing the ability of interest rate policy instruments to achieve inflation targeting in the domestic market as well. As a conclusion and proposals for further development of policies in the financial sector to ensure the sustainable development of small open economies is systematized a list of possible regulatory measures. It is emphasized that the development of regulatory policies in the monetary and financial spheres in small open economies, which includes Ukraine, should be implemented comprehensively and include the development of macroprudential tools to limit systemic risk factors, suppress illicit capital flows and reduce the role of psychological factors of pro-cyclical behavior. The implementation of regulatory measures on transparent terms in such spheres will not make free-market self-regulatory mechanisms weaken, but rather helps to release them.